W SPRAWIE SYTUACJI PRAWNEJ CZŁONKÓW KORPUSU SŁUŻBY CYWILNEJ NA PODSTAWIE PRZEPISÓW USTAWY O SŁUŻBIE CYWILNEJ Z 2006 R. - Samol, Sebastian (Wydział Prawa i Administracji UAM, 2007)
The paper focuses on the conditions o f employment of civil servants under the new regulations and provisions of the Act on civil service of 24 August 2006 (Dz. U. No 170, item 1218). The author analyses the new provisions and their impact on the conditions of employment in civil service, the rights and duties of civil servants, the rules governing remuneration of civil servants and their disciplinary liability, as well as the constitutionality o f the provisions of the Act on civil service 2006. The above analysis constitutes the grounds upon which conclusions about the change of the legal status of that employees’ group are drawn.
LEGAL STATUS OF THE MEMBERS OF CIVIL SERVICE CORPS UNDER THE ACT ON CIVIL SERVICE OF 2006